Sensitivity of serum C-reactive protein (CRP) levels compared to white blood cell count (WBC) as a predictor of surgical site infection in patients undergoing major surgery - Felix Hangandi; . Supomo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Early diagnosis and treatment of infections is essential in the care of the surgical patients. Rapidand appropriate diagnosis for an infection can prevent irrational use of antibiotics in the surgicalcare. A blood culture is a standard method to detect and identify bacteria causing the infections.However, it is time-consuming to confirm the results. Therefore, an alternative method thatsensitive and specific to reduce the time necessary to confirm the laboratory report is urgentlyneeded. The aim of this study was to compare the sensitivity and specificity of C-reactiveprotein (CRP) with white blood cell (WBC) count as a predictor of surgical site infection (SSI) inpatients who underwent major surgery. This was a descriptive analytical study with a prospectiveobservational design involving patients who underwent major surgery in Department of Surgery,Dr. Sardjito General Hospital, Yogyakarta between Octobers until December 2011. On the thirdday post operative surgery, serum CRP level and WBC were measured. In addition, bacterialculture from the surgical wound of patients who suffered SSI, according to Centers for DiseaseControl (CDC) criteria, was performed. Among 49 patients who involved in this study, 16patients (32.7%) suffered from SSI consisting 12 cases of superficial SSIs and 4 cases of deepSSIs. Among 9 patients who had an abnormal WBC count, 6 patients experienced SSI, whileamong 9 patients who had CRP serum levels above 8 mg/dL, 7 patients suffered from SSI. Thesensitivity and specificity of serum CRP levels in predicting SSI was 43.75% and 93.93%,respectively. Whereas the sensitivity and specificity of WBC was 31.25% and 87.87%,respectively. In conclusion, CRP is more sensitive and specific than WBC in predicting SSI inpatients who underwent major surgery.